Facilitating Children's Club-Organized Sports Participation: Person-Environment Misfits Experienced by Parents from Low-Income Families - Lonneke van Leeuwen; Anne Annink; Kirsten Visser; Marielle Jambroes (MDPI AG, 2022)
Despite the many benefits of club-organized sports participation for children, studies have shown that sports participation is lower among children from low-income families than among children from middle- or high-income families. Adopting a socioecological perspective, the main aim of our study was to identify and describe experiences of person-environment (PE) misfits in relation to parental facilitation of children's sports participation. We conducted 24 interviews with parents from low-income families. PE misfits were found in multiple behaviors related to the facilitation of children's sports participation: financing sports participation; planning and investing time; transporting children; acquiring, processing, and providing information; and arranging support. Across these PE misfits, influential attributes were found on the individual level (e.g., skills) as well as within the social, policy, physical, and information environment. In response to PE misfits experienced, parents deployed multiple strategies to reduce these PE misfits, aimed at enhancing either themselves (e.g., increasing financial capacities) or their environments (e.g., arranging social support). These results provide an insight into experienced PE misfits that took the form of multiple specific behaviors which parents found difficult while facilitating their children's sports participation. Furthermore, the results provide insight into the environmental and individual attributes that were involved in these PE misfits, and into how parents modified themselves or their environments in order to make their environments more supportive. The study contributes to future research on individual and environmental influences on parental facilitation of their children's sports participation, as well as on the development of multilevel interventions aimed at increasing sports participation among children from low-income families.